Feeding status of free-range scavenging chickens in different agro-climatic regions of India. Issue 1 (2nd January 2020) - Prakash, B.; Verma, S. K.; Rama Rao, S. V.; Raju, M. V. L. N.; Paul, S. S.; Kannan, A.; Mishra, S.; Singh, V.; Sankhyan, V.
ABSTRACT: 1. The aim of this study was to determine the nutritional status of backyard chickens reared under 4 different agro-climatic conditions (tropical, humid subtropical, cool-temperate and semi-arid) of India during different seasons of the year and to compare their nutritional status with those reared under confined feeding system (CFS). In each season, 15 adult and 15 grower chickens were slaughtered for collecting content of crop and gizzard to assess the nutritional status from different agro-climatic conditions. 2. The dry matter content of crop and gizzard was higher ( P < 0.01) in chickens reared under backyard conditions compared to those reared under CFS. 3. Higher ( P < 0.01) crop and gizzard contents were recorded during winter compared to the rainy season. The proportion of grains in the crop during summer and winter season was higher compared to rainy season. Further, there were more insects present in the crop during the rainy season and winter compared to summer. 4. The proportion of insects was higher in chickens reared in humid, subtropical and cool temperate regions compared to semi-arid conditions. The consumption of grasses was higher in cool-temperate regions as compared to those reared under other areas. 5. Crude protein (CP), Ca, P and gross energy (GE) content of the crop were higher in chickens reared under CFS compared to those reared in backyard systems and CP in the crop contents was lower in backyard chickens reared in humid subtropical and semi-arid regions compared to other areas. Similarly, lower ( P < 0.01) Ca levels were seen in crop and gizzard contents from birds reared in semi-arid Rajasthan, and P and GE were lower in tropical wet and dry Telangana (TWT) compared to the chickens reared in the backyard conditions in other regions. 6. Based on the results, the nutrient intake for birds utilising the scavenging feed resource base (SFRB) in the TWT region was below the requirements of backyard chickens from the other regions selected in the present study. GE and CP were critically deficient in the SFRB of the TWT region. Therefore, evolving location-specific supplementary diets using locally available feed resources to meet nutrient requirement of backyard chickens is required for optimising production potential.